STRATIGRAFI SUSEPTIBILITAS MAGNETIK SINGKAPAN EMBUNG E SEBAGAI ACUAN INTERPRETASI BAWAH PERMUKAAN DI INSTITUT TEKNOLOGI SUMATERA - Nono Agus Santoso; M Rafif Pascaloa; Ahmad Zaenuddin (Jurnal Geosaintek, 2022)
Reference in interpretation is very important. We cannot always rely on the Telford table because each region has different physical parameters. The purpose of this study was to create a magnetic susceptibility stratigraphy of the Embung E outcrop with the hope that it could be used as a reference for subsurface interpretation at the Sumatran Institute of Technology (ITERA). The results obtained that the Embung E outcrop has a magnetic susceptibility stratigraphy consisting of soil, tuff and tuffan clay. Sequentially the magnetic susceptibility of the soil is about 5 – 90 × 10-8m3/kg, tuff is about 1-10 × 10-8m3/kg and the tuff clay is about 5 – 80 × 10-8m3/kg. This result can be used as a reference for interpretation because it has been correlated with geological observations of rocks in the field.